2020
DOI: 10.31234/osf.io/c8weq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Psychological Impact of Threat & Lockdowns During the COVID-19 Pandemic

Abstract: This study addressed the psychological impact of the COVID-19 pandemic on mental health and examined factors exacerbating or mitigating the negative effects of lockdown. Results from a large multi-country online survey (N=8,229) showed average elevated levels of anxiety and depression (especially in the USA, UK, and Brazil), associated with feelings of low control and social isolation. Although social isolation increased with the duration of quarantine, it was mitigated by frequent communication with close oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…4 , 13 They may have also been challenged by longer working hours and more intense working circumstances, sometimes with inadequate personal protective equipment (PPE), 14 , 15 the latter of which has been found to be associated with depressive and anxiety symptoms among keyworkers during the current pandemic. 16 Degree of exposure to the public and therefore to the virus may also correlate with increased distress in other keyworker roles as well. One US study conducted in the first few months of the pandemic found that grocery store workers who interacted directly with the public were more anxious and depressed than those who did not interface with customers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 , 13 They may have also been challenged by longer working hours and more intense working circumstances, sometimes with inadequate personal protective equipment (PPE), 14 , 15 the latter of which has been found to be associated with depressive and anxiety symptoms among keyworkers during the current pandemic. 16 Degree of exposure to the public and therefore to the virus may also correlate with increased distress in other keyworker roles as well. One US study conducted in the first few months of the pandemic found that grocery store workers who interacted directly with the public were more anxious and depressed than those who did not interface with customers.…”
Section: Introductionmentioning
confidence: 99%
“…b. General Certificate of Secondary Education (GCSE) typically taken at the age of 15 or 16; Advanced Level qualifications (A-levels) and other equivalent educational qualifications that are not part of higher education (typically age[16][17][18][19].…”
mentioning
confidence: 99%
“…We suggest this may reflect the fact that people consider scientists the authorities on COVID-19, rather than governments. Moreover, there is variation in how much governments are perceived to have taken action during the COVID-19 pandemic (van Mulukom et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4,13 They may have also been challenged by longer working hours and more intense working circumstances, sometimes with inadequate personal protective equipment (PPE), 14,15 the latter of which has been found to be associated with depressive and anxiety symptoms amongst key workers during the current pandemic. 16 Degree of exposure to the public and therefore to the virus may also correlate with increased distress in other key worker roles as well. One US study conducted in the first few months of the pandemic found that grocery store workers who interacted directly with the public were more anxiety and depressed than those who do not interface with customers.…”
Section: Introductionmentioning
confidence: 99%